Financial management analysis in the higher education institutions: experience from Universiti Malaysia Perlis (UniMAP) (2003-2012) - Mahamad, Nor Azlindamazlini (International digital organization for scientific information (IDOSI), 2016)
Higher education has been one of the key elements to boost country’s development in terms of economic growth, social status and citizen well-being.Through effective higher education systems, it will benefit the public as a whole as adequate education empowers people to gain knowledge, skills and talents in order to fulfill rapid demands in competitive market trends.The government has allocated a significant amount of the national budget into the education system and it is crucial for all public universities to coordinate its financial management efficiently. Considering that financial sustainability is critical for higher education, this conceptual paper is to examine how the public university operates their financial management whether they can manage public money with Good Governance Principles or otherwise.Specifically, this paper analyzes the financial assessment in which the case study conducted by the Annual Reports from Universiti Malaysia Perlis (UniMAP) in ten years starting from 2003 until 2012.The results showed how UniMAP generate the income either through consultation activities, holdings, conferences, short courses, research grants and how UniMAP spending its budget allocation for ten years in which the research findings revealed that there was surplus between 2003 until 2009 and 2011 until 2012, while in 2010, the result showed a deficit in its financial management.